2022
DOI: 10.7759/cureus.24926
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma With Cardiac Metastasis Presenting as Presyncope

Abstract: Hepatocellular carcinoma (HCC) is a common primary tumor of the liver that is highly invasive and can even invade the portal and hepatic veins in later stages. In this report, we present one such rare case of HCC invading the right atrium. A 69-year-old male patient recently diagnosed with HCC secondary to hepatitis C presented to the hospital after experiencing an episode of near syncope. On examination, he had a distended abdomen consistent with ascites with positive fluid shift, elevated jugular vein disten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are several case reports regarding HCC with cardiac involvement. Patients often presented with cardiac symptoms including dyspnea on exertion, lower extremity edema and orthopnea [16][17][18]. Imaging workup showed a mass in either the atrium or ventricle, often right-sided and laboratory markers showed elevated liver enzymes and an abnormal coagulation profile [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several case reports regarding HCC with cardiac involvement. Patients often presented with cardiac symptoms including dyspnea on exertion, lower extremity edema and orthopnea [16][17][18]. Imaging workup showed a mass in either the atrium or ventricle, often right-sided and laboratory markers showed elevated liver enzymes and an abnormal coagulation profile [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Patients often presented with cardiac symptoms including dyspnea on exertion, lower extremity edema and orthopnea [16][17][18]. Imaging workup showed a mass in either the atrium or ventricle, often right-sided and laboratory markers showed elevated liver enzymes and an abnormal coagulation profile [16][17][18]. A clinicopathologic study revealed 18 out of 439 cases of patients had HCC with cardiac involvement on autopsy [19].…”
Section: Discussionmentioning
confidence: 99%